1950
DOI: 10.1103/physrev.79.54
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Spectra and Molecular Structures of Methyl Cyanide and Methyl Isocyanide

Abstract: 181 1 ' Spartein . 2 THF kristallisieu in der monoklinen Raumgruppe P2,, u = 921.6(10), b =1766.7(10), r =1098(2)pm, fi =107.65(7)", V = 1703(4) A', Z = 2, Q~~~. =1.127 g~m -~ fur M = 577.8, p = 0.498 mm-'. An einem Kristall der GroBe 0.6 x 0.4 x 0.3 mm wurden auf einem EN- RAF-NONIUS-Vierkreisdiffraktometermit Graphit-monochromatisierter Cu,,-Strahlung bei 163 K 4606 Reflexe vermessen, von denen 4279 unabhingig (R,,, = 0.0533) und 3467 beobachtet ( F > 4u(F/) waren. Losung (PATSEE) [9] und Verfeinerung im SHE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
35
1

Year Published

1970
1970
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(42 citation statements)
references
References 8 publications
4
35
1
Order By: Relevance
“…We were surprised that the rotational constant as determined by the far-infrared data (both with and without the inclusion of the early microwave results) did not show better agreement with the result of Kessler et al (8). However, the 0.17-MHz discrepancy in B corresponds to a 6 -7 MHz difference in frequency for the transitions reported here, which is more than comfortably outside the measurement uncertainty.…”
contrasting
confidence: 41%
See 1 more Smart Citation
“…We were surprised that the rotational constant as determined by the far-infrared data (both with and without the inclusion of the early microwave results) did not show better agreement with the result of Kessler et al (8). However, the 0.17-MHz discrepancy in B corresponds to a 6 -7 MHz difference in frequency for the transitions reported here, which is more than comfortably outside the measurement uncertainty.…”
contrasting
confidence: 41%
“…In particular, the only published microwave spectrum for the molecule consists of two low-J rotational transitions, with fully tube into a liquid-nitrogen-cooled metallic vessel. Interestingly, Clothier et al (15) have reported an explosion of liquid methyl isocyanide at resolved K structure but no reported value for the D J centrifugal distortion constant (8). Thus, we report here the observation and analysis of high room temperature.…”
mentioning
confidence: 55%
“…Because the order parameter S zz may be readily extracted from highfield deuterium NMR spectra, the only remaining parameters for the dipole-dipole coupling strengths are the angles and distances that define the molecular geometry, which may be obtained from the literature [40].…”
mentioning
confidence: 99%
“…Although this procedure is equivalent to using only the change in the angle zt CCN, it seems easier to visualize the change of projection of each component of the inertia tensor as the molecule is bent in vibration. From basic considerations, the equations used to calculate the moments of inertia about the x-axis and the z-axis for the CH3CN molecule were developed by Kessler et al [5] before the symmetry is broken by vibration. These equations must be modified for the configuration of broken symmetry and to take into consideration the non-point-mass distribution of the three hydrogen atoms in the methyl group.…”
Section: Outline Of the Methodsmentioning
confidence: 99%
“…These equations must be modified for the configuration of broken symmetry and to take into consideration the non-point-mass distribution of the three hydrogen atoms in the methyl group. The formulas for the components of the inertia tensor for an arbitrary axis of rotation are [5,6,7] …”
Section: Outline Of the Methodsmentioning
confidence: 99%